Tactile Stimulation to Stimulate Spontaneous Breathing during Stabilization of Preterm Infants at Birth: A Retrospective Analysis - Dekker, Janneke; Martherus, Tessa; Cramer, Sophie J. E.; van Zanten, Henriette A.; Hooper, Stuart B.; te Pas, Arjan B. (Frontiers in Pediatrics, 2017)
Background and aims Tactile manoeuvres to stimulate breathing in preterm infants are recommended during the initial assessment at birth, but it is not known how often and how this is applied. We evaluated the occurrence and patterns of tactile stimulation during stabilisation of preterm infants at birth. Methods Recordings of physiological parameters and videos of infants <32 weeks gestational age were retrospectively analysed. Details of tactile stimulation during the first 7 minutes after birth (timing, duration, type and indication) were noted. Results Stimulation was performed in 164/245 (67%) infants. The median (IQR) GA was 28 6/7 (27 2/7 – 30 1/7) weeks, birth weight 1153 (880 – 1385) grams, Apgar score at 5 minutes was 8 (7 – 9), 140/245 (57%) infants were born after caesarean section and 134/245 (55%) were male. There were no significant differences between the stimulated and the non-stimulated infants with regard to basic characteristics. In the stimulated infants, the first episode of stimulation was given at a median (IQR) of 114 (73-182) seconds after birth. Stimulation was repeated 3 (1-5) times, with a median (IQR) duration of 8 (4-16) seconds and a total duration of 32 (15-64) seconds. Modes of stimulation were: rubbing (68%) or flicking (2%) the soles of the feet, rubbing the back (12%), a combination (9%) or other (8%). In 67% of the stimulation episodes, a clear indication was noted (25% bradycardia, 57% apnoea, 48% hypoxemia, 43% combination) and an effect was observed in 18% of these indicated stimulation episodes. A total effect of all stimulation episodes per infant remains unclear, but infants who did not receive stimulation were more often intubated in the delivery room (14/79 (18%) vs 12/164 (7%), p<0.05). Conclusion There was a large variation in the use of tactile stimulation in preterm infants during stabilisation at birth. In most cases there was an indication for stimulation, but only in a small proportion an effect could be observed.